Introduction to NJWLS 2018-2 - Buch, Anders (Nordic Journal of Working Life Studies, 2018)
The Greek philosopher Heraclitus famously claimed that the only thing that is con- stant is change. Heraclitus made this claim in ancient Greece 2500 years ago, in a society that we—by contemporary measures at least—consider to be a fairly stable society governed by traditions and standards that held sway for centuries. In modern reflexive (Beck, Giddens, and Lash 1994) and liquid modernity (Bauman 2000), how- ever, it seems that the pace of change has increased tremendously. So much in fact, that the protagonist of Guiseppe Tomasi de Lampedusa’s novel ‘The Leopard’ (2007) stated that nowadays everything must change in order to stay the same. Hartmut Rosa (2015) has theorized the state of modern society as that of social acceleration – social life, and work, has been speeded up and dynamized so that we have to go faster and faster just to accomplish status quo (...)